A water-stable lanthanide-functionalized MOF as a highly selective and sensitive fluorescent probe for Cd2+1. Issue 36 (4th May 2015) - Hao, Ji-Na; Yan, Bing
<x xml:space="preserve">Abstract</x> A highly selective and sensitive fluorescent sensor for Cd2+ in aqueous solution based on a lanthanide post-functionalized metal–organic framework was developed.